Fitness Center Design with Natural Shapes and Forms Approach in Surabaya - Pande Putu Dwi Novigga Artha (Architectural Research Journal, 2021)
Density of Surabaya city affects the physical and psychological health of the people. Productive activities accompanied by a dense environment mean that people rarely have time to exercise. To increase the awareness and interest of the people of the city of Surabaya to exercise, it is necessary to have a sports facility with a special approach. Biophilic theory, especially the natural shapes and form approach, can be a solution to these problems. The return of nature's essence into the building can provide positive benefits for human physical and physical health. Previous research has discussed the determination of fitness center design criteria with the natural shapes and forms approach in Surabaya. In this follow-up journal, we will discuss the final result or application of the design criteria into an architectural work. The design method used is the force based framework method. The force in the design of this building in addition to the surrounding natural environment is the natural perception of the community which is transformed into architectural forms. It aims to increase interest in training and restoring the user's physical and psychological health without having to go far out of town to look for nature.